Applications, synthesis and characterization of gold nano particles - Islam, Zareef Al; Mondal, Shuvo; Islam, Md. Inzamamul (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.